Differences in physiological traits and protein expression between glyphosate-tolerant glandless cotton and its wild type - CHEN, XIANHONG; BAH, ALIEU MOHAMED; LIN, LI; ZHU, SHUIJIN; WU, FEIBO (The Indian Journal of Agricultural Sciences, 2014)
Physiological traits and proteomic expression were compared between EPSPS-G6 transgenic glyphosate-tolerant glandless upland cotton (GT) and its non-transgenic wild type (non-GT). GT showed higher net photosynthetic rate at boll setting stage (BSS) than non-GT, with higher stomatal conductance (gs), intercellular CO2 concentration (Ci) and transpiration rate (E) at the beginning of boll open stage (BBOS), but lower in Ci at BSS. Contents of chlorophyll a, chlorophyll b and chlorophyll a+b in GT were uniformly significantly less than those in non-GT at BSS and BBOS. Insertion of EPSPS gene had altered uptake of mineral nutrients: GT demonstrated less concentrations in N, Mg and K, but higher in P, Ca, Fe, K, Cu, Mn and Zn compared with non-GT. Contents of soluble sugar at BSS and BBOS and soluble protein at PFS and BSS in GT were significantly higher than non-GT; but GT had lower soluble sugar content at PFS and soluble protein at squaring stage. GT recorded significantly higher activities in superoxide dismutase and catalase, but lower in peroxidase and ascorbate peroxidase compared with non-GT. Proteomic alteration in leaves of GT vs non-GT was analyzed using 2-DE coupled with mass spectrometry. Eleven differentially expressed proteins were identified, of which 7 and 4 spots being up- and down- regulated, respectively. GT showed up-regulated expression of RuBisCO large subunit, CP4EPSPS, and ATP synthase, but down-regulated glutamate-1-semialdehyde-2, 1-aminomutase and manganesestabilising protein, respectively.